Sifat Mekanik Beton Berpori Dengan Material Agregat Buatan Dari Limbah Plastik PET: Mechanical Properties Of Porous Concrete With Artificial Aggregate Material From PET Plastic Waste - M. Zulham; Liliana Liliana; Frieda Frieda (Media Ilmiah Teknik Sipil, 2022)
The use of plastic without any recycling action from human hands will result in the accumulation of plastic waste that damages the environment. Making plastic waste as an artificial aggregate is one way to overcome it. This research was conducted using an experimental method, namely by substituting natural aggregate with artificial aggregate of 58% in porous concrete. Aggregate:cement ratio used is 6:1 and 7:1 with variations of FAS used are 0.25 and 0.30. The tests carried out are compressive tests, tensile tests, and porosity tests. From the results of the compressive strength test, the maximum compressive strength was 6.700 kg/cm2 in the mixture used, namely 58% artificial aggregate: 42% natural aggregate, 6:1 aggregate:cement ratio, and 0.30 FAS. In the tensile strength test, the largest tensile strength was 0.802 kg/cm2 in the mixture used, namely 58% artificial aggregate: 42% natural aggregate, 6:1 aggregate:cement ratio, and 0.30 FAS. While the porosity test obtained the largest porosity of 5.04 in the mixture used, namely 58% artificial aggregate: 42% natural aggregate, 7:1 aggregate:cement ratio, and 0.25 FAS. The porous concrete in this study did not meet the specifications for the road body because it had a small compressive strength and a small tensile strength